Analisis Faktor – Faktor Yang Mempengaruhi Penghindaran Pajak Penipuan - Sari, Fangela Myas; Dewi, Siska; Rokhman, Nur (Akuisisi : Jurnal Akuntansi, 2024)
This research aims to find out whether research examining financial pressure, education level and internal control systems can influence tax avoidance and Fraud. Previous research used quantitative research and the data still used secondary data. The advantage of this research is that this research is different from previous research because this research uses primary data. This research is different from previous research because it combines education level systems and financial pressures that can influence tax avoidance and Fraud. This research method uses primary data and is processed using the Smart PLS 3.0 data processing application